INFLUENCE OF STRENGTH TRAINING ON ELDERLY AUTONOMY (Fiep Bulletin - online, 2011)
The aging process leads to several body changes. Thus it is necessary to search for ways to mitigate the negative effects of this involution. Therefore, knowing that the improved strength of the subjects represents a greater availability of these for daily activities, the aim of this study, was to investigate in strength training, evidence of improvements in variables related to it, and compare the possible improvement in beginners and elderly already practitioners of a program with this character. Were performed between 12 weeks of training, a pre and post-assessment, in which were measured variables as weight, height, BMI, waist, hip, WHR and %fat. Were also conducted tests of strength with a manual and a lower limbs dynamometer, and functional capacity tests such as climbing stairs and self-perceived performance of activities of daily living (ADL). The sample consisted of 30 subjects of both genders, with a mean age of 62,5 years (± 2,5), with 14 of them being already practitioners of the modality (G1) and 16 beginners in the practice of strength training (G2). The results revealed significant differences in pre-test between G1 and G2 for functional variables in the test of stair climbing and self-perception of ADL, for manual strength and for the anthropometric variable %fat. After 12 weeks, both groups had positive results caused by strength training, but G1 has reached G2, because none of the variables in the post-test had significant difference between groups. It's possible to conclude that elderly subjects maintain their capacity of adaptability and trainability; furthermore, the training should be modified to keep providing long-term results.
Keywords: Strength training; elderly; autonomy